Little Metalmark, Calephelis virginiensis (Guérin-Ménéville) (Insecta: Lepidoptera: Riodinidae) - Donald W. Hall; Marc Minno; Jerry F. Butler (EDIS)
EENY-407, a 4-page illustrated fact sheet by Donald W. Hall, Marc Minno, and Jerry F. Butler, is part of Featured Creatures collection. It provides information about this tiny orange butterfly with metallic silver lines on the wings. Includes references. Published by the UF Department of Entomology and Nematology, May 2007.